THE ROLE OF ACCOUNTING INFORMATION SYSTEMS AND BLOCKCHAIN IN IMPROVING PUBLIC SECTOR ACCOUNTABILITY IN INDONESIA - Sabar Jaya Mendrofa; Oktarini Khamilah Siregar (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
Accountability in public sector financial management is a central issue in promoting transparency and efficiency in governance, particularly at the regional and village levels. This study aims to analyze the role of Accounting Information Systems (AIS), blockchain technology, and e-Budgeting in strengthening public financial accountability in Indonesia. The method used is a qualitative literature review of eight relevant scientific documents and community service activities. The study results show that the implementation of an AIS (SIA) such as SISKEUDES (Village-Based Financial Information System) has been proven to improve the efficiency of village financial recording and reporting. Furthermore, e-Budgeting plays a crucial role in digital and transparent budget planning, while also opening up opportunities for public participation. Meanwhile, blockchain technology holds significant potential for creating a secure and tamper-proof real-time audit system, although its implementation still faces technical and regulatory hurdles. This study concludes that the synergy between SIA, e-Budgeting, and blockchain technology can create a more transparent, accountable, and technologically adaptive public financial governance ecosystem. Strengthening human resources, digital training, and integrated policy support are needed to optimize technology implementation in the Indonesian public sector.